Mapping and Measuring Place Attachment to the Coastline of Famagusta - Koç, Özge Selen (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Implementing an urban development strategy by improving the quality of the physical environment could be a potential development model, however, in the case of ignorance of social and psychological values, this potential may harm the city and citizen relationship. Therefore, the bond established between the city and the citizen should be taken into consideration. This bond has a multi-dimensional complex structure and it should be supported by the concept of place attachment. Place attachment is defined as the emotional bonds that individuals establish with their meaningful physical and social environment as a result of their social and individual interactions. Thus, it could be said that the place attachment-based urban development model could be an effective development strategy. This study focuses on people’s interaction with a coastline which is one of the most important components of city of Famagusta. There have been many important turning points during the history of the Famagusta, and as a result of them, the relationship between Famagusta, as well as its citizens with the sea has been changed due to some restrictions (such as military occupations, unorganized transportation, poor urban development, location of the commercial port etc.). This study aims to develop people waterfront relationship in the Famagusta through the selected citizens’ patterns of place attachment and analyses degree of these attachments. Famagusta is a multicultural city due to its extensive student population coming from various countries and tourist. Therefore, the city has a fluid population. On the other hand, today there are mainly two homogenous groups of citizens which are the ones who were born and grow-up in the city before and after the fragmentation of the island in 1974. Therefore, the interaction of these two local groups with the city is decisive for the future of the city. The study wants to reflect the attachment patterns of people, from two generations of citizens, who took part in many social responsibility projects related to the current structure and problems of the city. The study aims to introduce an initial guideline for future waterfront regeneration projects based on the research findings.

ÖZ: Fiziksel çevrenin kalitesini artırarak kentsel gelişim stratejisinin uygulanması potansiyel bir gelişim modeli olarak varsayılabilir, Ancak, sosyal ve psikolojik faktörlerin etkisinin göz ardı edilmesi durumunda bu olası potansiyel, şehir ve vatandaş ilişkisine zarar verebilir. Bu nedenle şehir ile kullanıcısı arasında kurulan bağ dikkate alınmalıdır. Bu bağ çok boyutlu karmaşık bir yapıya sahiptir ve yer bağlılığı kavramı ile desteklenmelidir. Mekana bağlılık, bireylerin sosyal ve fiziksel çevreleriyle etkileşimlerinin bir sonucu olarak, kurdukları duygusal bağlar olarak tanımlanmaktadır. Bu nedenle, yer bağımlılığına dayalı kalkınma stratejisinin etkili bir kentsel kalkınma modeli olabileceği söylenebilir. Bu çalışma, İnsanların Gazimağusa kentinin en önemli bileşenlerinden biri olan sahil şeridi ile etkileşimlerine odaklanmaktadır. Gazimağusa kentinde tarih boyunca birçok önemli dönüm noktası yaşanmıştır ve bunların bir sonucu olarak Gazimağusa kenti ile vatandaşları arasındaki ilişki bazı nedenlerden ötürü kısıtlandırılmıştır. (askeri alanlar, toplu taşıma eksikliği, yetersiz kentsel gelişme, ticari limanın konumu vb.). Bu çalışmanın amacı, Seçilen vatandaşların mekansal bağlılıklarının ölçülmesi ve analiz edilmesi sonucu insan-kıyı şeridi ilişkisinin geliştirilmesidir. Gazimağusa, çeşitli ülkelerden gelen geniş öğrenci nüfusu ve turist sayısı nedeniyle çok kültürlü bir şehirdir. Bu nedenle kentte değişken bir nüfus var. Öte yandan bugün 1974'te adanın ikiye bölünmesinde, önce ve sonra şehirde doğup büyüyen iki homojen vatandaş grubu bulunmaktadır. Bu nedenle bu iki yerel grubun kent ile etkileşimi kentin geleceği için daha sağlam ve belirleyici nitelikte olduğu söylenebilir. Çalışmada, kentin mevcut yapısı ve sorunları ile ilgili birçok sosyal sorumluluk projesinde yer alan iki farklı kuşağın bağlanma modelleri yansıtmak istenmiş ve elde edilen sonuçlara göre, gelecekteki kıyı yenileme projeleri için bir kılavuzu oluşturmayı amaçlamaktadır.
Master of Science in Urban Design. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2020. Supervisor: Asst. Prof. Dr. Ceren Boğaç
Keywords: Architecture Department; Urban Design; Place Attachment--Environmental psychology--Attachment behavior--Famagusta (Cyprus (Turkish Republic of Northern Cyprus, 1983-)); Place attachment--Psychological aspects; Place Attachment, A Tripartite Organizing Framework, Waterfronts Development Strategies